THE LAW ON THE DIALECTICAL RELATIONSHIP BETWEEN PRODUCTIVE FORCES AND PRODUCTION RELATIONS AND THE CURRENT APPLICATION OF THIS LAW IN VIETNAM (Isagoge - Journal of Humanities and Social Sciences, 2021)
The history of society's development is the history of movement and development, the interchange ability of socio-economic forms from low level to high one. The movement and development of socio-economic forms is due to the dialectical mutual interaction between productive forces and production relations, between infrastructure and superstructure. In this article, the author analyzes the basic contents of the law on the dialectical relationship between productive forces and production relations and the current application of this law in Vietnam. The results show that the practical requirements of the process of building socialism in Vietnam today reveal that the problem of perceiving and creatively applying the law of the dialectical relationship between productive forces and production relations is an urgent requirement, and this is also a way to protect and develop the theory of Marxism-Leninism, thereby making it really vital, persuasive and guide our actions to the chosen destination, which is to successfully build socialism.
Keywords: Law; Dialectical relationships; Productive forces; Production relations; Vietnam